Degradable calcium phosphate-coated porous zinc scaffold combined with platelet-rich plasma implantation for rabbit radius defect - Xing Wang; Wanxiong He; Sile Hu; Rui Bai; Chao Sun; Ting Hao; Fei Xue; Zhiwei Pei; Hui Wei; Yonggang Wu; Chenyang Meng; Guanghui Liu; et al. (European Journal of Medical Research)
Abstract Bone defects seriously affect patients' quality of life and are difficult to repair, and the use of biodegradable porous scaffolds for bone defect repair has gradually become a hot spot in the field of bone repair. The porous biodegradable metal scaffold constructed with Zn covered with calcium and phosphorus coating is a high-quality bone repair material. However, rapid bone defect repair cannot be achieved only by the trace elements Ca, P, and Zn, which are beneficial to bone regeneration, so a material that promotes bone regeneration must be compounded. Platelet-rich plasma is a class of liquid complexes that can promote bone regeneration, and its composite with biodegradable metal scaffolds can solve the problem of the lack of mechanical load bearing of platelet-rich plasma in bone defects. In this study, a porous Zn scaffold was prepared by hot-press sintering of NaCl template, and a calcium phosphate coating was prepared by chemical deposition strategy, and the scaffold was made by compositing it with stable platelet-rich plasma via Poloxamer 407, and the in vitro and in vivo studies on the scaffold's biocompatibility and osteogenesis were carried out using the rabbit radial bone defect model. The results showed that the biodegradable porous scaffold/PRP composite scaffold had good biocompatibility and no cytotoxicity. It can promote osteogenic differentiation and calcium deposition of rabbit BMSCs in vitro and also promote the formation of new bone around the scaffold in vivo. The biodegradable porous scaffold/PRP composite scaffold has a good application prospect in bone defect repair.